La aplicación de herramientas tecnológicas en la atención al usuario en las notarías del Cantón Quito. - Zapata Esquivel, Norma Marlene (2021)
This document had as its central point the social and legal research associated with Resolution 001-2021 of the Council of the Judiciary, which refers to the implementation of technological tools in notaries in order to guarantee continuity in the provision of services to the public, in the context of the COVID-19 pandemic. For the fulfillment of this purpose, the research raised as a general objective to analyze the impact on the notaries of the Quito canton Resolution 001-2021, issued by the Council of the Judiciary, in relation to the implementation of an autonomous digital platform for the provision of notarial services to its users; that together with the formulation of the specific objectives of identification of the rectory of the Council of the Judiciary, the description of the current situation of notaries and the research on the belonging of having a technological platform, sought to align the document towards a normative and propositional process, in order to establish a social reality focused on the legal nature of the resolution issued by the competent body. The methodological proposal established a qualitative research with a territorial focus in the canton Quito, as an instrument for collecting information, interviews were used with notaries, in order to receive their opinion as directly involved in the object of study.